Faktor Yang Mempengaruhi Dividend Payout Policies Pada Perusahaan Manufaktur Di BEI - Ariel Yoga Pradipta, Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this study is to empirically examine the influence of corporate debt, corporate size, sales growth, and ROA on dividend payout policies in manufacturing industry that listed in BEI from the period 2017 – 2019. Sample selected using purposive sampling method with total 104 data from 38 companies. Data processing techniques using multiple regression analysis. This research used EViews 10 and Microsoft Excel 2016 to analyse the data. The result shows that corporate size and ROA have a positive significant effect on dividend payout policies. Corporate debt and sales growth have a negative insignificant effect on dividend payout policies. The research implication shows the importance of management to manage finances more effectively and efficiently, so that they are able to earn profits and be able to distribute dividends to attract investors to invest.